Spatial Resolution of a small animal PET scanner using 68Ga isotope - Victoria M. Garcia; A. C. M. Silva; Rodrigo Modesto Gadelha Gontijo; Andréa Vidal Ferreira (Brazilian Journal of Radiation Sciences)
Nuclear Medicine is a modality that has been growing a lot in Brazil and in the world, bringing new radiopharmaceuticals and technologies for the diagnosis and treatment of diseases, making them more effective and accurate. In the development of new radiopharmaceuticals for use in positron emission tomography (PET), the preclinical studies step largely uses PET scanners dedicated to small animals. To achieve this, quality control tests must be carried out to ensure the efficiency of the equipment. Thus, this work aimed to evaluate the spatial resolution of the small animals PET scanner of the CDTN using the isotope 68Ga. In this sense, a microPET hot rod phantom and a commercial 68Ge/68Ga generator were used to obtain PET images. The analysis of the 68Ga-PET images of the simulator was carried out qualitatively and quantitatively and revealed that the spatial resolution of the system using the 68Ga is 3.5 mm.